BEWEGLICHE KLAVIERSTUNDE. DIE INTEGRATION DER BEWEGUNG IN DEN KLAVIERUNTERRICHT - MAROSVÁRI, Dorottya (Studia Universitatis Babes-Bolyai Musica, 2017)
Moving Piano Lesson. The Integration of the Movement in the Piano Lesson. This paper presents the relationship of music and motion in the method of Émile Jaques-Dalcroze and dr. Géza Kovács, as well as introducing the techniques of the age-old Chinese martial art form of Taijiquan. The paper describes specific movements to achieve flexibility and relaxed posture that are fundamental for effective music practice. The author gives examples from her own teaching methods, complementing piano playing movements with other types of advantageous motions.